(untitled) (Journal of actual problems of jurisprudence, 2019)
The article provides for improving the quality of legal education, including- Les teaching on the requirements for the moral qualities of the employees of the law profile, on the legal culture of law enforcement. Keywords: lawyer, ethics, morality, law, conscience, responsibility.